FAKTOR FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERDIDIK KABUPATEN/KOTA DI BALI - Urtalina, Faga Arta; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 10, Oktober 2018 (pp. 2071-2308), 2018)
Unemployment in the Bali province tends mostly come from the workforce with senior high school level both general or vocational, and Bachelor degree compared with the level of junior and elementary education. This is due to the lack of synchronization between educational planning as well as available employment from the higher level of education owned by the workforce will be higher also aspirasinya to get a more appropriate position or employment opportunities. The purpose of this study was to investigate the effect both simultaneously and partially the minimum wage, economic growth, investment, and the proportion of working age population to uneducated unemployed regency or city in Bali province. This study uses multiple linear regression analysis and using secondary data. Based on the test results, simultaneously minimum wage, economic growth, investment, and proportion of working age population simultaneously affect the educated unemployed regency or city in Bali Province. Partially the minimum wage, economic growth, and investment have a negative and significant effect and the proportion of the working age population has a positive and significant impact on the unemployed educated regency or city in Bali province.